2002
DOI: 10.1051/0004-6361:20021324
|View full text |Cite
|
Sign up to set email alerts
|

The interstellar $\mathsf{{\vec C}_3}$ chain molecule in different interstellar environments

Abstract: Abstract.We present an analysis of spectra of six stars taken with high resolution (R = 220 000). The stars are reddened by molecular clouds that differ by the relative strength of the 5797 and 5780 diffuse interstellar bands (DIBs). The high signal-to-noise ratio of the spectra (S /N ≈ 700-1000) shows that the abundance of the linear molecule C 3 with respect to E B−V varies considerably from one star to an other. There is no correlation with E B−V . The strong variations in the abundance of C 3 must therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
0
18
1
Order By: Relevance
“…In the dense ISM the presence of C 3 was proven using its mid-and far-infrared vibrational transitions. 7, 9, 11 C 3 was also identified in the diffuse interstellar medium, first by Maier et al 8 and later in several other studies 12,13 along different lines of sight.…”
Section: Introductionmentioning
confidence: 76%
“…In the dense ISM the presence of C 3 was proven using its mid-and far-infrared vibrational transitions. 7, 9, 11 C 3 was also identified in the diffuse interstellar medium, first by Maier et al 8 and later in several other studies 12,13 along different lines of sight.…”
Section: Introductionmentioning
confidence: 76%
“…2 The identity of the carrier as C 3 was proved unambiguously by the 13 C isotope work of Douglas, 3 and later rotational analyses by Gausset et al 4,5 showed that the bands represent a 1 ⌸ u − 1 ⌺ g + transition of a linear molecule, where the lower state is the ground state. 2,[10][11][12][13] One of the interesting features of these spectra 2 is that the R͑0͒ line of the 000-000 band at 4051 Å was "uniformly underpopulated relative to what was expected from a thermal distribution that fitted J = 2-10." For example, the ground state has an unusually low bending frequency of 63.416 529͑40͒ cm −1 , 6,7 which, as discussed by Walsh, 8 is a result of its having no g electrons to provide a "backbone."…”
Section: Introductionmentioning
confidence: 94%
“…Roueff et al (2002) applied their sophisticated C 3 excitation model to all three of the detections by Maier et al (2001)-Oph, Per, and 20 Aql-along with their own observations of HD 210121, but none of the observations determined the population of C 3 in J > 14 well enough to constrain the full excitation model. Galazutdinov et al (2002) have since provided spectra of C 3 toward Oph and HD 152236, without analysis of the excitation.…”
Section: Introductionmentioning
confidence: 99%